Power and pacing calculations based on real-time locating data from a cross-country skiing sprint race - Swarén, M.; Eriksson, A. (Sports Biomechanics, 2019)
Pacing strategies in cross-country skiing have been investigated in several studies. However, none of the previous studies have been verified by collected skiing data giving the skiing velocities along a measured track. These can be used to calculate the propulsive power output. Collected real-time positioning data from a cross-country sprint skiing race were used to estimate the propulsive power by applying a power balance model. Analyses were made for the time-trial and the final for one female and one male skier. The average propulsive power over the whole race times were 311 and 296 W during the time trial and 400 and 386 W during the final, for the female and male skier, respectively. Compared to the average propulsive power over the whole race, the average active propulsive phases were calculated as 33 and 44% higher in the time trials and 36 and 37% higher in the finals for the female and male, respectively. The current study presents a novel approach to use real-time positioning data to estimate continuous propulsive power during cross-country sprint skiing, enabling in-depth analyses of power output and pacing strategies.